The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11070922
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia-Head Chondroitin Sulfate Protects against Nonalcoholic Fatty Liver Disease via Modulating the Gut–Liver Axis in High-Fat-Diet-Fed C57BL/6 Mice

Abstract: We isolated and characterized tilapia-head chondroitin sulfate (TH-CS) and explored its biological activity and mechanisms of action as an oral supplement for nonalcoholic fatty liver disease (NAFLD) induced by a high-fat diet (HFD) in mice. The results showed that treatment with TH-CS for 8 weeks alleviated the development of NAFLD, as evidenced by the notable improvement in liver damage, blood lipid accumulation and insulin resistance (IR). Meanwhile, TH-CS treatment reduced the expression of proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…These results suggest that the increased liver weights and macrovesicular fatty change of the hepatocytes in the HFrD group were caused by the accumulation of triglycerides in the liver. In other words, the daily consumption of excessive fructose for 4 weeks induced a typical NAFLD-like situation, as seen in other reports (12,33,34). In this study, periportal vacuolation in the hepatocytes was observed in the HFrD group after 4-weeks consumption (Table II).…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest that the increased liver weights and macrovesicular fatty change of the hepatocytes in the HFrD group were caused by the accumulation of triglycerides in the liver. In other words, the daily consumption of excessive fructose for 4 weeks induced a typical NAFLD-like situation, as seen in other reports (12,33,34). In this study, periportal vacuolation in the hepatocytes was observed in the HFrD group after 4-weeks consumption (Table II).…”
Section: Discussionsupporting
confidence: 87%
“…AMPK serves as a regulator for both anabolic and catabolic pathways. Activated AMPK decreases lipogenesis in the liver by inhibiting SREBP-1c expression [49,50]. PPAR-α is a nuclear hormone receptor involved in the regulation of lipid metabolism and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting analysis was performed based on previous study 29 . The total protein concentration in the supernatant of mice brain tissue homogenates was quantified using the BCA protein assay kit (Jiancheng Bioengineering Institute, Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting analysis was performed based on previous study. 29 The total protein concentration in the supernatant of mice brain tissue homogenates was quantified using the BCA protein assay kit (Jiancheng Bioengineering Institute, Nanjing, China). An equal amount of denatured protein from each brain tissue sample was separated by sodium dodecyl sulfate polyacrylamide-gel electrophoresis and transferred to polyvinylidene fluoride membranes.…”
Section: Western Blotting Analysismentioning
confidence: 99%